EFFECT OF DIFFERENT HOUSING SYSTEMS ON REPRODUCTIVE DISORDERS AND PERFORMANCE IN CROSSBREED COWS (Indian Journal of Animal Production and Management, 2015)
The effect of housing systems on reproductive disorders and performance were studied on Sixteen advanced pregnant Holstein Fresian cows and randomly divided equally into two groups of eight animals each (Group A as under conventional tie barn housing system and Group B as under loose housing system). Both the groups were reared under similar system of feeding and management except housing system. Most of the major parameters of reproductive disorder and reproductive performance showed non-significant (P < 0.05) differences between conventional and loose housing system. Total cost involved per day was significantly higher (P < 0.05) in case of conventional housing when compared with loose housing system. Cost of fodder, treatment and miscellaneous items were did not differ significantly between housing system. Average weekly milk production was significantly higher (P
Keywords: Reproductive disorder; Reproductive performance; Housing